2015
DOI: 10.1152/ajprenal.00126.2015
|View full text |Cite
|
Sign up to set email alerts
|

Nephron-specific deletion of the prorenin receptor causes a urine concentration defect

Abstract: The prorenin receptor (PRR), a recently discovered component of the renin-angiotensin system, is expressed in the nephron in general and the collecting duct in particular. However, the physiological significance of nephron PRR remains unclear, partly due to developmental abnormalities associated with global or renal-specific PRR gene knockout (KO). Therefore, we developed mice with inducible nephron-wide PRR deletion using Pax8-reverse tetracycline transactivator and LC-1 transgenes and loxP flanked PRR allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
72
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 45 publications
10
72
0
Order By: Relevance
“…Expression levels of (P)RR in the kidney were up-regulated in rats with congestive heart failure or chronic renal failure due to 5/6 nephrectomy (Hirose et al , 2010. Ramkumar et al (2015) showed that nephron-specific deletion of the (P)RR caused a urine concentration defect, and suggested that nephron (P)RR can potentially modulate renal water excretion. We have recently reported that high salt intake upregulates (P)RR expression in rat nephron (Rong et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Expression levels of (P)RR in the kidney were up-regulated in rats with congestive heart failure or chronic renal failure due to 5/6 nephrectomy (Hirose et al , 2010. Ramkumar et al (2015) showed that nephron-specific deletion of the (P)RR caused a urine concentration defect, and suggested that nephron (P)RR can potentially modulate renal water excretion. We have recently reported that high salt intake upregulates (P)RR expression in rat nephron (Rong et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A functional role of PRR in regulating renal aquaporin 2 (AQP2) expression and urine-concentrating capability has been revealed by analysis of mice with conditional deletion of PRR in the nephron (15) and the CD (14). However, whether the antidiuretic action of CD PRR is conferred by sPRR remains elusive.…”
mentioning
confidence: 99%
“…26 Similarly, infusion of PRR short hairpin RNA in the renal medulla decreased expression of the epithelial sodium channel (ENaC) in rats (although the effect on BP was not examined). 32 To delineate the role of nephron PRR in BP regulation, we developed an inducible renal tubule PRR KO mouse 33 to avoid the deleterious effects of PRR deletion on organ development. Renal tubule PRR KO mice had similar BP as control mice under varying sodium intake but had an attenuated hypertensive response with reduced renal ENaC expression after Ang II infusion.…”
Section: Role Of the Prr In Bp Regulationmentioning
confidence: 99%
“…Renal tubular PRR also modulates water reabsorption through Ang II-dependent and Ang II-independent mechanisms. 33,[37][38][39] Recent studies have shown that the PRR regulates vasopressin-stimulated AQP2 expression via activation of prostaglandin EP4 receptor 39 and the Wnt/b-catenin pathway. 38 A fundamental question is whether the intercalated and/or principal cell PRR modulates renal sodium and water reabsorption.…”
Section: Role Of the Prr In Bp Regulationmentioning
confidence: 99%